ANALISIS NILAI TAMBAH DAN PENETAPAN HARGA SELAI NANAS GORENG DENGAN METODE COST PLUS PRICING DI KABUPATEN MUARO JAMBI - Tang, Becek; Alamsyah, Zulkifli; Ningsih, Rozaina (Agros Journal of Agriculture Science, 2024)
This research aims to (1) describe the description of the fried pineapple jam agroindustry in Muaro Jambi Regency, (2) analyze the Added Value of fried pineapple jam in Muaro Jambi Regency and (3) analyze Cost Plus Pricing pricing using the Full Costing Approach. The data analysis method used is a descriptive method using the Hayami Method value added analysis auxiliary table and using the Cost Plus Pricing Method. Based on the results of the Cost Plus Pricing analysis, the mark up for fried pineapple jam for wholesale sales is an average of IDR 63,333 / kg and the retail sales price is IDR. 100,000/Kg, the average profit and mark up is currently IDR 34,879.77 for wholesale sales and retail sales of IDR. 52,627.95 agro-industry already uses high mark ups, there is a large difference from the sales price. If the agro-industry is willing to reduce it to 75.73%, the price for wholesale sales will be Rp. 50,000 and retail sales use a mark up of 89.99, the price is Rp. 90,000, this will increase competitiveness in the market, causing production and sales to increase, profits will be high.